2022
DOI: 10.1038/s41598-022-10755-2
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the structure and function of the human organic anion transporter 1 in lipid bilayer membranes

Abstract: The human SLC22A6/OAT1 plays an important role in the elimination of a broad range of endogenous substances and xenobiotics thus attracting attention from the pharmacological community. Furthermore, OAT1 is also involved in key physiological events such as the remote inter-organ communication. Despite its significance, the knowledge about hOAT1 structure and the transport mechanism at the atomic level remains fragmented owing to the lack of resolved structures. By means of protein-threading modeling refined by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…The definition of the co-substrate and substrate required a parametrization using GAFF2 and DNA.OL15 forcefield's parameters, considering the latter being a purine derivative. MD simulations were performed using a similar setup as previously established [15]. The simulations were carried out with using the CPU and GPU codes of the Amber18 package [40], [41].…”
Section: Simulation Setupmentioning
confidence: 99%
See 4 more Smart Citations
“…The definition of the co-substrate and substrate required a parametrization using GAFF2 and DNA.OL15 forcefield's parameters, considering the latter being a purine derivative. MD simulations were performed using a similar setup as previously established [15]. The simulations were carried out with using the CPU and GPU codes of the Amber18 package [40], [41].…”
Section: Simulation Setupmentioning
confidence: 99%
“…The comparison of the intracellular structural arrangement between OF and IF apo hOAT1 models revealed that the charge-relay system must be disrupted along transport cycle. This might ultimately unlock the IC gating required for substrate release [15]. Conformational changes are expected to be triggered upon substrate and/or co-substrate binding, suggesting the existence of a distant communication between substrate binding pockets and MFS conserved intracellular motifs.…”
Section: Allosteric Communication Between the Substrate Binding Pocke...mentioning
confidence: 99%
See 3 more Smart Citations